(untitled) (London, 2000)
Environmental Risks and the Media explores the ways in which environmental risks, threats and hazards are represented, transformed and contested by the media. At a time when popular conceptions of the environment as a stable, "natural" world with which humanity interferes are becoming increasingly contested, the media's methods of encouraging audiences to think about environmental risks--from the "mad cow" crisis to global warming--are becoming more and more controversial. Examining large-scale disasters as well as "everyday" hazards, the contributors consider the tensions between entertainment and information in media coverage of the environment. The issues explored include: how the media frame "expert," "counter-expert" and "lay public" definitions of environmental risk; the role played by environmental pressure groups like Greenpeace in shaping media coverage; and the media's emphasis on spectacular events at the expense of issue-sensitive reporting.
Keywords: Environmental protection